Influence of knowledge and Family Support for Stroke Patient Neurorehabilitation Obedience in Medical Rehabilitation Unit RSUDZA Banda Aceh - Syarifah, Chaira; Syahrul .; Rachmat Hidayat (Jurnal Ilmiah Mahasiswa Kedokteran Medisia, 2016)
Stroke is a loss of brain function cause of circulatory disorders of the brain, so that the patient will suffer paralysis or death. Post-stroke changes will lead to physical limitations that would become a form of disability in patients and lead to the patient's self-image is disturbed, unproductive, dependence on others. Efforts that can be made include neuro rehabilitation programs or treatments of stroke include physical therapy and exercise to control patient’s movement in order to prevent stiffness and immobility. Research conducted in RSUP.DR. M.Djamil, stated that there are several variables that affect the obedience of post-stroke patients to undergo neuro rehabilitation programs, includes the knowledge, support, and motivation of patient’s family. This research aims to determi ne the effect of knowledge and family support towards patient’s obedience undergoing post -stroke neuro rehabilitation in this RSUDZA. This research was used a  cross-sectional design by  accidental sampling method, that have been collected totaled 40 respondents in October-November 2015. The analysis used in this research was the Mann-Whitney test, the results obtained p-value of 0.000 (p0.05) to the effects of variable knowledge and obtained p-value of 0.002 (p0.05) against the influence of family support variable. It is concluded that there is influence between knowledge and family support with obedience of neuro rehabilitation in RSUDZA Banda Aceh 2015